13. The Examination of Borax in Beef Meatballs in Pidie Jaya (123 PEMERIKSAAN KANDUNGAN BORAKS PADA BAKSO DAGING SAPI DI KABUPATEN PIDIE JAYA) - Rizal Fuadi (Jurnal Medika Veterinaria, 2016)
This study was aimed to determine the presence of borax in beef meatballs in Pidie Jaya. This study used 20 samples of beef meatballs which were randomly selected from 4 districts in Pidie Jaya: District Meureudu, Meurah Dua, Bandar Dua, and Trienggadeng. Samples were collected from 5 sampling sites in each district in the afternoon at 17:00 to 19:00 pm. Borax examination was carried out using borax kit test. Data were analyzed descriptively. The results showed that borax was not found in beef meatballs collected from four districts in Pidie Jaya. ____________________________________________________________________________________________________________________ Key words: beef meatballs, borax, Pidie Jaya